Functional Role of miR-499a-5p in the Development of Gastric Cancer - Lu, Cuiling; Guo, Chengwang; Wu, Cuihua; Zhang, Liping; Liu, Xiaoling; Guo, Shoucun (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Gastric cancer (GC) is a highly prone malignant tumor, which has attracted wide attention. This study investigated the expression and clinical value of miR-499a-5p in GC. Materials and Methods: A total of 105 patients with GC were included in this study. Simultaneously, 55 patients with benign stomach disorders and 45 healthy subjects were enrolled as controls. Real-time quantitative polymerase chain reaction was used to determine the expression of miR-499a-5p. The receiver operating characteristic curve was used to assess the diagnostic value of miR-499a-5p in GC. Kaplan–Meier and logistic analyses were used to evaluate the association between miR-499a-5p and GC prognosis. Results: The levels of miR-499a-5p are markedly downregulated in GC and have a high diagnostic value. miR-499a-5p is closely linked to pathological features of GC. Overexpression of miR-499a-5p inhibits GC cell growth, migration, and invasion. Furthermore, miR499a-5p is also related to GC and 5-year survival, and is a risk factor for GC death. Conclusion: The levels of miR-499a-5p were markedly downregulated in GC and related to GC pathological features. It has the potential to become a biomarker for the diagnosis of GC. Cite this article as: Lu C, Guo C, Wu C, Zhang L, Liu X, Guo S. Functional role of miR-499a-5p in the development of gastric cancer. Turk J Gastroenterol. 2025;36(1):45-52.